Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1186/s12876-020-01561-z
|View full text |Cite
|
Sign up to set email alerts
|

Sedation practices for routine gastrointestinal endoscopy: a systematic review of recommendations

Abstract: Background Sedation is commonly used in gastrointestinal endoscopy; however, considerable variability in sedation practices has been reported. The objective of this review was to identify and synthesize existing recommendations on sedation practices for routine gastrointestinal endoscopy procedures. Methods We systematically reviewed guidelines and position statements identified through a search of PubMed, guidelines databases, and websites of rele… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 44 publications
1
46
0
6
Order By: Relevance
“…36 In our study, we adopted a 1:1 EP mixture to allow longer examination time and stimulation needed for colonoscopy compared with gastroscopy. 6 A previous study reported that 70% of the usual dose could be administered to complete endoscopy in elderly patients, although the number of remediations was…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…36 In our study, we adopted a 1:1 EP mixture to allow longer examination time and stimulation needed for colonoscopy compared with gastroscopy. 6 A previous study reported that 70% of the usual dose could be administered to complete endoscopy in elderly patients, although the number of remediations was…”
Section: Discussionmentioning
confidence: 99%
“…5 Propofol, etomidate, and midazolam combined with opioids are the most commonly used drugs globally for sedation during endoscopic procedures. 6 However, each drug has both advantages and disadvantages. The disadvantage of propofol is injection pain, aspiration pneumonia due to loss of protective reflexes, lack of an analgesic effect and specific antagonists, risk of developing propofol infusion syndrome and bacterial contamination, metabolic acidosis, a narrow therapeutic index (which increase the risk of hypoxia), and cardiovascular and respiratory depression, especially when combined with opioids.…”
Section: Introductionmentioning
confidence: 99%
“…The sedation of patients to reduce pain, reduce anxiety and provide amnesia facilitates uncomfortable diagnostic procedures such as endoscopy ( Dossa et al, 2021 ) and interventional procedures such as those employed in cardiology ( Makkad, 2013 ). Several clinical trials of remimazolam as a sedative agent for procedural sedation have been conducted.…”
Section: Remimazolammentioning
confidence: 99%
“…Single propofol boluses were administered in order to reach the desired sedation level. Following the German and ESGE guidelines for sedation in gastrointestinal endoscopy, a moderate sedation level was targeted for colonoscopy procedures ( 26 , 27 ). The additional administration of midazolam was allowed in accordance with national sedation guidelines ( 4 ).…”
Section: Methodsmentioning
confidence: 99%